Constructong (ad)ventures in collaborative composing: examining a case of (un)sanctioned play in the elementary classroom (New Jersey: Wiley Company, 2023)
The author highlights children's play as a creative literacy practice and a complex and collaborative one; she specifically showcases children's strategic use of (un)sanctioned play to foster personally meaningful literacies.
Keywords: Literacy. -- Classroom